General disease symptoms and their impact on appetite and food intake in older hospitalized patients - Maryam Pourhassan; Diana Daubert; Lars Sieske; Chantal Giehl; Nina Rosa Neuendorff; Rainer Wirth (Appetite, 2026)

Chronic anthropogenic disturbances reorganize tropical dry forest biota - Elâine M.S. Ribeiro; Rainer Wirth; Marcelo Tabarelli; Inara R. Leal (Trends in Ecology & Evolution, 2026)

Cognitive decline limits compensatory resource allocation within the aged swallowing network - Sonja Suntrup-Krueger; Paul Muhle; Janna Slavik; Jonas von Itter; Andreas Wollbrink; Rainer Wirth; Tobias Warnecke; Rainer Dziewas; Joachim Gross; Sven G. Meuth; Bendix Labeit (GeroScience, 2025)
Cognitive decline has been postulated to predispose to presbyphagia but the neurophysiological basis of this interaction is unclear. To investigate the role of cognition for compensatory resource allocation within the swallowing network and behavioral swallowing performance in dual-task cognitive and motor interference in ageing, volunteers ≥ 70 years of age without preexisting diseases causing dysphagia were investigated using Flexible Endoscopic Evaluation of Swallowing (FEES) including a cognitive and motor dual-task paradigm and a Montreal Cognitive Assessment. The neural correlates of swallowing during dual-task were characterized using magnetoencephalography. Results were related to cognitive function. Sixty-three participants (77.7 ± 6.1 years) underwent FEES, of which 40 additionally underwent MEG. Both cognitive and motor dual-tasks interfered with swallowing function resulting in an increase in pharyngeal residue and premature bolus spillage. The extent of swallowing deterioration (“dual-task cost”) was associated with cognitive decline (cognitive dual-task: Spearman’s rho = − 0.39, p = 0.002; motor dual-task: Spearman’s rho = − 0.25, p = 0.046). When challenged with dual-tasking participants with regular cognition showed compensatory stronger and broader brain activation in cortical pre- and supplementary motor planning areas as well as in frontal executive regions within the cortical swallowing network ( p = 0.004) compared to participants with cognitive deficits. They also performed better in the competing cognitive and motor dual-task and showed fewer incorrect responses ( p = 0.028). Oropharyngeal swallowing involves cognitive cortical processing. Cognitive decline seems to limit the capacity for compensatory resource allocation within the swallowing network. This may lead to deterioration in both swallowing function and concurrent cognitive-motor performance in challenging dual-task situations.

Use of woody species in the Caatinga dry forest may lead to higher vulnerability to extirpation: An assessment based on ethnobiological, reproductive and conservation criteria - Jéssica Luiza S. Silva; Maria Fabíola Barros; Kátia F. Rito; Oswaldo Cruz-Neto; Marcelo Tabarelli; Inara R. Leal; Ulysses Paulino Albuquerque; Rainer Wirth; Ariadna Valentina Lopes (Flora, 2024)

Simulated soil erosion predominantly affects fungal abundance in the rapeseed rhizosphere - Julian Ruggaber; Ayten Pehlivan; Rainer Remus; Davide Francioli; Stephan Wirth; Jürgen Augustin; Steffen Kolb (Rhizosphere, 2024)

Divergent reproductive responses of Caatinga dry forest plants to leaf-cutting ant herbivory - Isabelle L.H. Silva; Fernanda M.P. Oliveira; Talita Câmara; Rainer Wirth; Ariadna V. Lopes; Inara R. Leal (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Rapid recovery of ant-mediated seed dispersal service along secondary succession in a Caatinga dry forest - Francisca R. Oliveira; Fernanda M.P. Oliveira; Diego Centeno-Alvarado; Rainer Wirth; Ariadna V. Lopes; Inara R. Leal (Forest Ecology and Management, 2024)

Root but not shoot litter fostered the formation of mineral-associated organic matter in eroded arable soils - Eva Kaštovská; Michal Choma; Gerrit Angst; Rainer Remus; Jürgen Augustin; Steffen Kolb; Stephan Wirth (Soil and Tillage Research, 2024)

Coppicing as a driver of plant resprouting and the regeneration of a Caatinga dry forest - Ronald Noutcheu; Fernanda M.P. Oliveira; Rainer Wirth; Marcelo Tabarelli; Inara R. Leal (Forest Ecology and Management, 2023)

Aridity, but not disturbance, reduces the specialization and modularity of plant–insect herbivore interaction networks in Caatinga dry forest - Pedro E. Santos-Neto; Xavier Arnan; José D. Ribeiro-Neto; Rainer Wirth; Inara R. Leal (Journal of Insect Conservation, 2022)

Correction to: Habitat fragmentation and forest management alter woody plant communities in a Central European beech forest landscape - Kevin Wilhelm Bähner; Marcelo Tabarelli; Burkhard Büdel; Rainer Wirth (Biodiversity and Conservation, 2021)

Habitat fragmentation and forest management alter woody plant communities in a Central European beech forest landscape - Kevin Wilhelm Bähner; Marcelo Tabarelli; Burkhard Büdel; Rainer Wirth (Biodiversity and Conservation, 2020)
Habitat fragmentation and forest management have been considered to drastically alter the nature of forest ecosystems globally. However, much uncertainty remains regarding the causative mechanisms mediating temperate forest responses, such as forest physical environment and the structure of woody plant assemblages, regardless of the role these forests play for global sustainability. In this paper, we examine how both habitat fragmentation and timber exploitation via silvicultural operations affect these two factors at local and habitat spatial scales in a hyper-fragmented landscape of mixed beech forests spanning more than 1500 km 2 in SW Germany. Variables were recorded across 57 1000 m 2 plots covering four habitats: small forest fragments, forest edges within large control forests, as well as managed and unmanaged forest interior sites. As expected, forest habitats differed in disturbance level, physical conditions and community structure at plot and habitat scale. Briefly, diversity of plant assemblages differed across all forest habitats (highest in edge forests) and correlated with integrative indices of edge, fragmentation and management effects. Surprisingly, managed and unmanaged forests did not differ in terms of species richness at local spatial scale, but managed forests exhibited a clear signal of physical/floristic homogenization as species promoted by silviculture proliferated; i.e. impoverished communities at landscape scale. Moreover, functional composition of plant communities responded to the microclimatic regime within forest fragments, resulting in a higher prevalence of species adapted to these microclimatic conditions. Our results underscore the notion that forest fragmentation and silvicultural management (1) promote changes in microclimatic regimes, (2) alter the balance between light-demanding and shade-adapted species, (3) support diverse floras across forest edges, and (4) alter patterns of beta diversity. Hence, in human-modified landscapes edge-affected habitats can be recognized as biodiversity reservoirs in contrast to impoverished managed interior forests. Furthermore, our results ratify the role of unmanaged forests as a source of environmental variability, species turnover, and distinct woody plant communities.

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Foraging Leaf-Cutting Ants Learn to Reject Vitis vinifera ssp. vinifera Plants that Emit Herbivore-Induced Volatiles - Theresa Thiele; Christian Kost; Flavio Roces; Rainer Wirth (Journal of Chemical Ecology, 2014)

TiO2 exsolution from garnet by open-system precipitation: evidence from crystallographic and shape preferred orientation of rutile inclusions - Alexander Proyer; Gerlinde Habler; Rainer Abart; Richard Wirth; Kurt Krenn; Georg Hoinkes (Contributions to Mineralogy and Petrology, 2013)

Intracrystalline microstructures in alkali feldspars from fluid-deficient felsic granulites: a mineral chemical and TEM study - Lucie Tajčmanová; Rainer Abart; Richard Wirth; Gerlinde Habler; Dieter Rhede (Contributions to Mineralogy and Petrology, 2012)

The advantage of growing on moss: facilitative effects on photosynthetic performance and growth in the cyanobacterial lichen Peltigera rufescens - Claudia Colesie; Sarah Scheu; T. G. Allan Green; Bettina Weber; Rainer Wirth; Burkhard Büdel (Oecologia, 2012)

Grain boundary and volume diffusion experiments in yttrium aluminium garnet bicrystals at 1,723 K: a miniaturized study - Katharina Marquardt; Elena Petrishcheva; Emmanuel Gardés; Richard Wirth; Rainer Abart; Wilhelm Heinrich (Contributions to Mineralogy and Petrology, 2011)

Volume diffusion of Ytterbium in YAG: thin-film experiments and combined TEM–RBS analysis - Katharina Marquardt; Elena Petrishcheva; Rainer Abart; Emmanuel Gardés; Richard Wirth; Ralf Dohmen; Hans-Werner Becker; Wilhelm Heinrich (Physics and Chemistry of Minerals, 2010)

Symplectite formation during decompression induced garnet breakdown in lower crustal mafic granulite xenoliths: mechanisms and rates - Júlia Dégi; Rainer Abart; Kálmán Török; Enikő Bali; Richard Wirth; Dieter Rhede (Contributions to Mineralogy and Petrology, 2010)

How leaf-cutting ants impact forests: drastic nest effects on light environment and plant assemblages - Michele M. Corrêa; Paulo S. D. Silva; Rainer Wirth; Marcelo Tabarelli; Inara Roberta Leal (Oecologia, 2010)

IR calibrations for water determination in olivine, r-GeO2, and SiO2 polymorphs - Sylvia-Monique Thomas; Monika Koch-Müller; Patrick Reichart; Dieter Rhede; Rainer Thomas; Richard Wirth; Stanislav Matsyuk (Physics and Chemistry of Minerals, 2009)

Insight into the proteome of the hyperthermophilic Crenarchaeon Ignicoccus hospitalis: the major cytosolic and membrane proteins - Tillmann Burghardt; Manfred Saller; Sonja Gürster; Daniel Müller; Carolin Meyer; Ulrike Jahn; Eduard Hochmuth; Rainer Deutzmann; Frank Siedler; Patrick Babinger; Reinhard Wirth; Harald Huber; et al. (Archives of Microbiology, 2008)

Non-specific association between filamentous bacteria and fungus-growing ants - Christian Kost; Tanja Lakatos; Ingo Böttcher; Wolf-Rüdiger Arendholz; Matthias Redenbach; Rainer Wirth (The Science of Nature, 2007)